A theoretical study of the A(2)Sigma(+)-X-2 Pi system of the SiP molecule - Ornellas, F. R.; Andreazza, C. M.; de Almeida, A. A. (Univ Chicago Press, 2000)
The A (2)Sigma(+) and X(2)Pi electronic states of the SiP species have been investigated theoretically at a very high level of correlation treatment (CASSCF/MRSDCI). Very accurate potential energy curves are presented for both states, as well as the associated spectroscopic constants as derived from the vib-rotational energy levels determined by means of the numerical solution of the radial Schrodinger equation. Electronic transition moment function, oscillator strengths, Einstein coefficients for spontaneous emission, and Franck-Condon factors for the A(2)Sigma(+)-X(2)Pi system have been calculated. Dipole moment functions and radiative lifetimes for both states have also been determined. Spin-orbit coupling constants are also reported. The radiative lifetimes for the A(2)Sigma(+) state, taking into account the spin-orbit diagonal correction to the X(2)Pi state, decrease from a value of 138 ms at v' = 0 to 0.48 ms at v' = 8, and, for the X(2)Pi state, from 2.32 s at v = 1 to 0.59 s at v = 5. Vibrational and rotational transitions are expected to be relatively strong.
Keywords: ISM : molecules; molecular data; molecular processes